Recent advances in biosensors for analysis of DNA/RNA methylation - Zhensheng Ma; Yue Hu; Lina Wang; Mimi Li; Chenghong Li; Lulu Li; Hui Huang; Lichao Fang; Xiaolong Wang; Huamin Liu; Junsong Zheng (Sensing and Bio-Sensing Research)
DNA and RNA methylation are essential epigenetic modifications that play a pivotal role in various physiological processes by modulating gene expression at the post-transcriptional level. Abnormal DNA/RNA methylation is closely linked to a range of human diseases, including cancer and neurological disorders. Therefore, the accurate and sensitive detection of DNA/RNA methylation is of great importance in both epigenetic biology research and disease diagnosis. Technological advancements have led to the comprehensive development of methylation detection methods. Among these, electrochemical techniques have garnered significant attention owing to their simplicity and effectiveness in detection. This review provides an overview of methylation detection technologies based on electrochemical principles developed over the past five years, including electrochemical, photoelectrochemical, electrochemiluminescence, and fluorescence methodologies. Additionally, it discusses the advantages and disadvantages of these approaches, challenges and advancements in methylation detection.